Hyaluronan inhibits expression of ADAMTS4 (aggrecanase-1) in human osteoarthritic chondrocytes. Issue 6 (28th July 2008) - Yatabe, T; Mochizuki, S; Takizawa, M; Chijiiwa, M; Okada, A; Kimura, T; Fujita, Y; Matsumoto, H; Toyama, Y; Okada, Y
Abstract : Background: Intra-articular injection of hyaluronan (HA) has been suggested to have a disease-modifying effect in osteoarthritis, but little is known about the possible mechanisms. Objective: To investigate the effects of HA species of different molecular mass, including 800 kDa (HA800) and 2700 kDa (HA2700), on the expression of aggrecanases (ie, ADAMTS species), which play a key role in aggrecan degradation. Methods: The effects of HA species on the expression of ADAMTS1, 4, 5, 8, 9 and 15 in interleukin 1α (IL1α)-stimulated osteoarthritic chondrocytes were studied by reverse transcription PCR and real-time PCR. Expression of ADAMTS4 protein and aggrecanase activity and signal transduction pathways of IL1, CD44 and intracellular adhesion molecule 1 (ICAM1) were examined by immunoblotting. Results: IL1α treatment of chondrocytes induced ADAMTS4, and HA800 and HA2700 significantly decreased IL1α-induced expression of ADAMTS4 mRNA and protein. IL1α-stimulated aggrecanase activity in osteoarthritic chondrocytes was reduced by treatment with HA2700 or transfection of small interfering RNA for ADAMTS4. A similar result was obtained when HA2700 was added to explant cultures of osteoarthritic cartilage. HA2700 neither directly inhibited nor bound to ADAMTS4. Downregulation of ADAMTS4 expression by HA2700 was attenuated by treatment of IL1α-treated chondrocytes with antibodies to CD44 and/or ICAM1. The increased phosphorylation of IL1 receptor-associated kinase-1 and extracellular signal-regulated protein kinase1/2 induced by the IL1α treatment was downregulated by enhanced IRAK-M expression after HA2700 treatment. Conclusion: These data suggest that HA2700 suppresses aggrecan degradation by downregulating IL1α-induced ADAMTS4 expression through the CD44 and ICAM1 signalling pathways in osteoarthritic chondrocytes.